2019
DOI: 10.1080/15384101.2019.1704512
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR-155-5p facilitates enterovirus 71 replication through suppression of type I IFN response by targeting FOXO3/IRF7 pathway

Abstract: Enterovirus 71 (EV71), the major cause of hand-foot-and-mouth disease (HFMD), has evolved diverse strategies to counter the type I interferon (IFN-I) response during infection. Recently, microRNAs have regulatory roles in host innate immune responses to viral infections; however, whether EV71 escapes the IFN-I antiviral response through regulation of miRNAs remains unclear. Using a microarray assay, microRNA-155-5p (miR-155-5p) was found to be significantly up-regulated in serum from patients with EV71 infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…3A, B). Several reports support that the miRNA expression varies in different viral infections, even the change in the virus strain affects the miRNA expression [ 33 , 40 , 51 53 ]. PTEN is widely known for its role as a tumour suppressor and regulation of immune responses [ 28 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…3A, B). Several reports support that the miRNA expression varies in different viral infections, even the change in the virus strain affects the miRNA expression [ 33 , 40 , 51 53 ]. PTEN is widely known for its role as a tumour suppressor and regulation of immune responses [ 28 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, miR-30a packaging by exosomes targeted MyD88 and inhibited type I IFN production by promoting EVA71 replication in human oral epithelial cells [ 102 ]. In addition, upregulated miR-526a positively regulates RIG-I-dependent type I IFN production, and increased miR-155-5p negatively regulated the forkhead box protein O3 (FOXO3)/IRF7 axis to affect type I IFN production during EVA71 infection [ 56 , 103 ]. The overexpression of miR-9-5p suppressed RIG-I-mediated NF-κB signaling in several EVA71-infected cell lines [ 83 ].…”
Section: The Impact Of Ncrnas On Host Innate Immune Responses Indumentioning
confidence: 99%
“…Recently, it was found that gga-miR-155-5p could also target caspase-6 (an apoptosis executor) and FOXO3a (which induces cell cycle arrest in the G0/G1 phase) to inhibit apoptosis and accelerate the cell cycle, thus improving the viability of REV-infected CEFs [95]. In addition, hsa-miR-155-5p was also found to inhibit enterovirus 71's (EV71) replication through the promotion of the I-IFN response by targeting the FOXO3/IRF7 pathway [96]. Conversely, miR-155-5p may act as a villain to reinforce viral infections.…”
Section: Gga-mir-155-5pmentioning
confidence: 99%